2015
DOI: 10.1021/acs.orglett.5b00979
|View full text |Cite
|
Sign up to set email alerts
|

Facile Rh(III)-Catalyzed Synthesis of Fluorinated Pyridines

Abstract: A Rh(III)-catalyzed C–H functionalization approach was developed for the preparation of multi-substituted 3-fluoropyridines from α-fluoro-α,β-unsaturated oximes and alkynes. Oximes substituted with aryl, heteroaryl and alkyl β-substituents were effective coupling partners, as were symmetrical and unsymmetrical alkynes with aryl and alkyl substituents. The first examples of coupling α,β-unsaturated oximes with terminal alkynes was also demonstrated and proceeded with uniformly high regioselectivity to provide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Synthesis of pyridines 171 from α, -unsaturated oximes 170. [66] researchers for construction of different fluorinated molecules. Sosnovskikh et al reported an interesting application of such a reaction for the synthesis of CF 3 -pyridines 174.…”
Section: Fluorinated Heterodienesmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of pyridines 171 from α, -unsaturated oximes 170. [66] researchers for construction of different fluorinated molecules. Sosnovskikh et al reported an interesting application of such a reaction for the synthesis of CF 3 -pyridines 174.…”
Section: Fluorinated Heterodienesmentioning
confidence: 99%
“…Similarly, α,β‐unsaturated oximes 170 were applied by Ellman et al for the straightforward synthesis of polysubstituted monofluoropyridines 171 by Rh‐catalyzed cycloaddition with acetylenes (Scheme ) . The reaction is highly regioselective in the case of terminal acetylenes, but provided mixtures of regioisomers from non‐symmetrically disubstituted alkynes.…”
Section: Fluorine‐containing 13‐dienesmentioning
confidence: 99%
“…In 2015, Chen et al gave a protocol for the preparation of multi-substituted 3-fluoropyridines from α-fluoro-α,β-unsaturated oximes and alkynes using a Rh( iii )-catalyzed C–H functionalization approach. 209 Diversity in compounds synthesized was shown using oximes with various substituents which were coupled with substituted internal alkynes as well as terminal alkynes. Coupling of α,β-unsaturated oximes 318 with terminal alkynes 319 which gave single 3-fluoropyridine regioisomers 320 with high regioselectivity was also reported as the first examples of such a type for the synthesis of pyridine by Rh( iii ) catalysis using terminal alkynes (Scheme 58).…”
Section: Miscellaneous Fluorinated Building Blocksmentioning
confidence: 99%
“…In the first one, from 2013, [134] a α , β ‐unsaturated oxime is successfully converted into a furan derived with 89 % yield via a rhodium‐catalyzed C(sp 2 )−H activation. The same idea was applied two years later (2015) [135] to perform a rhodium‐catalyzed C(sp 2 )−H annulation in the presence of diethylacetylene. In both cases, the α , β ‐unsaturated oxime was also achieved via a condensation reaction with hydrochloric alkoxyamine (Scheme 20).…”
Section: N‐based Groupsmentioning
confidence: 99%